Nivolumab for malignant transformation of ovarian mature cystic teratoma - Kayoko Yoshimura; Koji Yamanoi; Masashi Kanai; Asuka Okunomiya; Yusuke Sagae; Masumi Sunada; Mana Taki; Masayo Ukita; Yoshitsugu Chigusa; Akihito Horie; Ken Yamaguchi; Junzo Hamanishi; et al. (Elsevier, 2022)
Mature cystic teratoma of the ovary (MCT) occasionally undergoes malignant transformation (MT) that is resistant to chemotherapy and has a poor prognosis. We experienced a case of clinically aggressive MCT-MT that invades surrounding organs and tissues. Although tumor was resected entirely, a rapid tumor recurrence occurred during postoperative chemotherapy (paclitaxel + ifosfamide + cisplatin). The results of comprehensive genomic profiling test performed early in the postoperative period showed a high tumor mutational burden of 23 mutations/Mb. Treatment with nivolumab monotherapy has promptly been initiated and has been very successful for more than one year.